2021
DOI: 10.1186/s13613-021-00889-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity in critical care publications: a novel Female First Author Index

Abstract: Background Bibliometric analyses show gender bias against women in scientific publications and citations. We hypothesized that a metric of an individual senior author’s inclusivity of women as first authors in critical care publications would predict gender inequality. Methods Using PubMed and Web of Science, we conducted a bibliometric analysis of original research publications in critical care from 2008 to 2018 in 11 specialty and general journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 38 publications
2
26
0
1
Order By: Relevance
“…When the senior author was a woman, the odds of women coauthors rose substantially, adjusted odds ratio 1.93 (95% CI 1.71-2.17). Chary et al (22) found similar results with significant variation by country for women as first authors, from 6.1% in Japan to 56.6% in Finland. The Canadian Critical Care Trials Group evaluated their publications and found that 37% of authors were women, 13.7% were from a visible minority group, 73% of articles included authors from more than one profession, and more than half were from more than one medical discipline (23).…”
Section: Medical Journalismsupporting
confidence: 69%
“…When the senior author was a woman, the odds of women coauthors rose substantially, adjusted odds ratio 1.93 (95% CI 1.71-2.17). Chary et al (22) found similar results with significant variation by country for women as first authors, from 6.1% in Japan to 56.6% in Finland. The Canadian Critical Care Trials Group evaluated their publications and found that 37% of authors were women, 13.7% were from a visible minority group, 73% of articles included authors from more than one profession, and more than half were from more than one medical discipline (23).…”
Section: Medical Journalismsupporting
confidence: 69%
“…Despite women comprising over half the US population and over half of US medical students since 2018 [ 25 ], women continue to be underrepresented in most surgical fields and as authors of scientific publications [ 20 , 26 , 27 ]. To better understand the ASE membership, we acquired gender data from ASE leadership.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing all abstracts, we used Gender API ( https://gender-api.com/ ), an “application programming interface (API)” software previously used in scientific and market research to estimate man or woman representation based on first name, to code first and last author genders [ 20 ]. The software classifies gender on a binary scale returning the terms “male,” “female,” or “unknown” based on an Internet search algorithm; however, we will use the terms “man” and “woman” in this manuscript to refer to gender as a social and behavioral construct distinct from chromosomal sex.…”
Section: Methodsmentioning
confidence: 99%
“…Os autores argumentam que essas descobertas têm implicações importantes para a visibilidade acadêmica e a vantagem cumulativa nas carreiras acadêmicas embora esses padrões possam resultar de diferenças no número de artigos que autores homens e mulheres publicaram, em vez de padrões específicos de gênero de comportamento de autocitação, essa diferença de gênero nas taxas de autocitação permaneceu estável nos últimos 50 anos, apesar do aumento representação das mulheres na academia. Chary et al (2021) comentam que as análises bibliométricas mostram o preconceito de gênero contra as mulheres em publicações e citações científicas. Em vista disso, hipotetizaram que o gênero de um autor sênior seria um preditor importante do gênero do primeiro autor.…”
Section: Gênero Na Ciência: Uma Breve Revisão De Literaturaunclassified